Daspu - Monti, Valentina (Italy, 2010)
A group of prostitutes in Rio de Janeiro, who fight to obtain rights and reduce stigma, create a clothing label that quickly invades Brazilian fashion shows.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films